The State-of-the-Art of the Humoral Memory Response to Snakebites: Insights from the Yanomami Population - Jati, Sewbert Rodrigues; dos Anjos Martins, Thais Andréa; Rocha, Anderson Maciel; Melo-dos-Santos, Guilherme [UNESP]; de Oliveira, Isadora Sousa; Ferreira, Isabela Gobbo; de Farias, Altair Seabra; Filardi, Eloise T. M. [UNESP]; Cerni, Felipe Augusto; Sartim, Marco Aurélio; de Almeida Gonçalves Sachett, Jacqueline; Monteiro, Wuelton Marcelo; et al. (My University, 2023)
Snakebite envenomation (SBE)-induced immunity refers to individuals who have been previously bitten by a snake and developed a protective immune response against subsequent envenomations. The notion stems from observations of individuals, including in the indigenous population, who present only mild signs and symptoms after surviving multiple SBEs. Indeed, these observations have engendered scientific interest and prompted inquiries into the potential development of a protective immunity from exposure to snake toxins. This review explores the evidence of a protective immune response developing following SBE. Studies suggest that natural exposure to snake toxins can trigger protection from the severity of SBEs, mediated by specific antibodies. However, the evaluation of the immune memory response in SBE patients remains challenging. Further research is needed to elucidate the immune response dynamics and identify potential targets for therapeutic interventions. Furthermore, the estimation of the effect of previous exposures on SBE epidemiology in hyperendemic areas, such as in the indigenous villages of the Amazon region (e.g., the Yanomami population) is a matter of debate.
Keywords: Amazon; antivenom; immune response; snakebite immunity; snakebite resistance; Yanomami